Differential localization of endothelin ETA and ETB binding sites in human placenta. - Rutherford, R. A. (Nature Publishing Group, 1993)
1. The localization and differential distribution of endothelin (ET) receptor subtypes (ETA and ETB) was investigated in sections of human placenta by use of quantitative in vitro autoradiography and receptor selective ligands. 2. Specific, high density [125I]-ET-1 binding sites were localized to the decidua and foetal membranes as well as to arteries and veins in the chorionic plate and throughout the villous tree. Moderate to low density binding was found in the extravillous and villous trophoblast respectively. 3. [125I]-ET-1 binding sites exhibited a rank order of inhibition by unlabelled peptide sequences (ET-1 > ET-3 > [Ala3,11,18Nle7]-ET-1 > BQ123 > or = sarafotoxin 6c). However, in contrast to the monophasic inhibition curve of ET-1, the other sequences produced a significantly better fit to a two component inhibition curve suggesting the presence of a heterogeneous population of ET binding sites. 4. ETA and ETB receptors were distinguished by competitive inhibition of [125]-ET-1 binding with increasing concentrations of unlabelled ET-3, [Ala3,11,18Nle7]-ET-1, sarafotoxin 6c and BQ123 and by incubating sections with the ETB agonist, [125I]-BQ3020. ET receptor subtypes exhibited a differential distribution in the placenta. ETA type binding sites predominated (approximately 80% of the total) on veins and arteries in the chorionic plate. Veins in stem villi, blood vessels in distal regions of the villous tree and decidual cells displayed a high density (approximately 60-70% of the total) of the ETB receptor subtype.(ABSTRACT TRUNCATED AT 250 WORDS)